ENHANCING MANAGERIAL CONTROL AND DECISION-MAKING IN MSMES THROUGH DIGITAL MONITORING SYSTEMS - Fullchis Nurtjahjani; Ade Ismail; Galih Putra Riatma; Asminah Rachmi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy, yet many continue to face challenges in business monitoring, coordination, and structured reporting. This study designs and evaluates a digital monitoring application tailored for the UMKM Corner community—a collaborative MSME group in Malang. Developed using a user-centered and community-based approach, the system supports daily transaction logging, product stock alerts, and real-time performance reporting through a coordinator dashboard. Field testing and TAM-based user evaluation reveal improvements in reporting consistency, internal coordination, and overall satisfaction. By emphasizing ease of use and managerial relevance, the application offers a replicable framework to strengthen group-based MSME governance and promote data-driven decision-making in similar business environments.